IMPLEMENTASI INTERNET OF THINGS SEBAGAI MONITORING SUHU PADA PEMANGGANG OTOMATIS BERBASIS ARDUINO UNO - Andreanus Calvin Hugo; Rahmat Hidayat; Lela Nurpulaela (Electro Luceat, 2020)
Internet of Things (IoT) is a structure where objects are provided with an exclusive identity and the ability to move data across a network without requiring two-way directions such as human to human, source to destination or human to computer interactions. IoT allows users and devices to be connected anytime, anywhere, and with anything. The purpose of this study is to determine how the IoT implementation works or the mechanism of the Arduino Uno based automatic grill using the Thermocouple sensor and the KY 026 Fire Sensor as the input. Based on the results of the research, it shows that NodeMCU can be connected with a distance of 60 meters from the source of the network source without any objects that can obstruct the internet connection and experience a delay of under one second at a distance of 35 meters.